Pion and kaon in the Beth-Uhlenbeck approach. (January 2016) - Dubinin, A.; Blaschke, D.; Radzhabov, A.
Abstract: In the present work the Mott effect for pions and kaons is described within a Beth- Uhlenbeck approach on the basis of the PNJL model. The contribution of these degrees of freedom to the thermodynamics is encoded in the temperature dependence of their phase shifts. A comparison with results from Nf = 2 + 1 lattice QCD thermodynamics is performed.